Antinociceptive activities of a novel diarylpentanoid analogue, 2-benzoyl-6-(3-bromo-4-hydroxybenzylidene)cyclohexen-1-ol, and its possible mechanisms of action in mice - Ong, Hui Ming; Ahmad Azmi, Ahmad Farhan; Sze, Wei Leong; Abas, Faridah; Perimal, Enoch Kumar; Omar Farouk, Ahmad Akira; Ahmad Israf, Daud; Sulaiman, Mohd Roslan (Nature Research, 2021)
A novel synthetic compound from the 2-benzoyl-6-benzylidenecyclohexanone analogue, namely 2-benzoyl-6-(3-bromo-4-hydroxybenzylidene)cyclohexen-1-ol (BBHC), showed pronounced nitric oxide inhibition in IFN-γ/LPS-induced RAW 264.7 cells. Based on this previous finding, our present study aimed to investigate the antinociceptive effects of BBHC via chemical and thermal stimuli in vivo. The investigation of the antinociceptive activity of BBHC (0.1, 0.3, 1.0 and 3.0 mg/kg, i.p.) was initiated with 3 preliminary screening tests, then BBHC was subjected to investigate its possible involvement with excitatory neurotransmitters and opioid receptors. The potential acute toxicity of BBHC administration was also studied. Administration of BBHC significantly inhibited acetic acid-induced abdominal constrictions, formalin-induced paw licking activity and developed notable increment in the latency time. BBHC’s ability to suppress capsaicin- and glutamate-induced paw licking activities, as well as to antagonise the effect of naloxone, had indicated the possible involvement of its antinociception with TRPV1, glutamate and opioid receptors, respectively. The antinociceptive activities of BBHC was not related to any sedative action and no evidence of acute toxic effect was detected. The present study showed that BBHC possessed significant peripheral and central antinociceptive activities via chemical- and thermal-induced nociceptive murine models without any locomotor alteration and acute toxicity.